Peptides as therapeutic agents for dengue virus - Chew, Miaw Fang *; Poh, Keat Seong; Poh, Chit Laa * (Ivyspring International Publisher, 2017)
Dengue is an important global threat caused by dengue virus (DENV) that records an estimated 390 million infections annually. Despite the availability of CYD-TDV as a commercial vaccine, its long-term efficacy against all four dengue virus serotypes remains unsatisfactory. There is therefore an urgent need for the development of antiviral drugs for the treatment of dengue. Peptide was once a neglected choice of medical treatment but it has lately regained interest from the pharmaceutical industry following pioneering advancements in technology. In this review, the design of peptide drugs, antiviral activities and mechanisms of peptides and peptidomimetics (modified peptides) action against dengue virus are discussed. The development of peptides as inhibitors for viral entry, replication and translation is also described, with a focus on the three main targets, namely, the host cell receptors, viral structural proteins and viral non-structural proteins. The antiviral peptides designed based on these approaches may lead to the discovery of novel anti-DENV therapeutics that can treat dengue patients.